2010
DOI: 10.2193/2008-442
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and Landscape Effects on Brood Parasitism, Nest Survival, and Fledgling Production in Swainson's Warblers

Abstract: Numerous factors, including nest predation and brood parasitism, may limit populations of neotropical migratory birds.However, nest predation and brood parasitism are not constant, and temporal, biological, habitat, and landscape factors can affect the likelihood of these events. Understanding these patterns is important for species of conservation concern for which managers seek to provide quality habitat. One such species, the Swainson's warbler (Limnothlypis swainsonii), is a neotropical migrant that breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 89 publications
0
19
1
Order By: Relevance
“…Parasitism by cowbirds is expected to increase with increasing fragmentation and forest edges (Goguen and Mathews 2000; Patten et al. 2006; Benson et al. 2010), and habitat changes over the past century appear to have been important precursors for parasitism of Black‐capped vireo broods.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Parasitism by cowbirds is expected to increase with increasing fragmentation and forest edges (Goguen and Mathews 2000; Patten et al. 2006; Benson et al. 2010), and habitat changes over the past century appear to have been important precursors for parasitism of Black‐capped vireo broods.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Furthermore, through our in-depth research on habitat use and demography we have consistently found new occupied locations at NF and WR in the vicinity of those locations that remained occupied between 2000 and 2004; these specific areas are free from the effects of flooding in most years and have supported Swainson's warbler populations for at least 10-20 and 40-50 years, respectively (Meanley 1971;Winker et al 2000;Graves 2002). We have detected no Swainson's warblers at sites previously determined to be unoccupied at SL and at few previously unoccupied sites at BR, only one of which had a Swainson's warbler detection in >1 year (Benson 2008). As a species that nests in the shrub layer and forages in leaf litter on the forest floor, Swainson's warblers are adversely affected by flooding.…”
Section: Discussionmentioning
confidence: 53%
“…Based on experiments with color-marked birds, surveying sites two times with playbacks yields a probability of detection of about 85% given that a bird is present (TJB, unpublished data). Moreover, as part of our ongoing research on habitat use and demography of Swainson's warblers, we returned to all of the sampled locations in 2005, and/or 2007(Anich et al 2009Benson et al 2010). Although the 2000/ 2001 surveys for Swainson's warblers (Bednarz et al 2005) focused on covering extensive areas and were therefore limited to roads, trails, and waterways, our in-depth studies involved repeated visits to these areas by multiple observers and were more thorough.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the Grinnellian niche space (i.e., the habitat characteristics needed for survival and reproduction) differed and was reduced in the selective harvest stand. While the harvested habitat provided increased complexity in the understory, the reduced complexity in the canopy may have contributed to reduced reproductive success by providing more open perches for avian nest predators and avian nest parasites (i.e., brown-headed cowbirds, Molothrus ater ) [53,54]. The reduced canopy complexity may have contributed to lower reproductive success in the harvested stand on the xeric ridge tops; while the greater understory vegetation complexity on the mesic slopes may have ameliorated the effects of avian predation and parasitism.…”
Section: Discussionmentioning
confidence: 99%